Sugakod an advocacy documentary film on anti-discrimination towards lesbians , gays, bisexuals and transgender (LGBT) - Requizo, Aljon Troy B.
Sugakod is an advocacy documentary film that deals with the issues that LGBT is facing ? which is discrimination. Because of discrimination in any forms, LGBT have the difficulty in communicating their concerns towards the heterosexuals. LGBTs view reality more objectively than those who are said to be superior which are the heterosexuals. This documentary serves as the medium for LGBTs to raise their marginalized voices. The contents of the documentary film are stories and experiences of the characters which are personally told by them. The documentary used the standpoint theory of Julia T. Wood and Sandra Harding as the framework in creating the concept of the documentary. Standpoint theory, rooted from the feminist movement, argues that the oppressed view of reality from the superior ? in this case, the LGBTs are the oppressed by the heterosexuals men and women. This documentary aimed to change the negative attitude and perception of heterosexuals towards the LGBT community and to help them to communicate their views on how the world is now. The making of the film undergone three stages: the pre-production, production, post-production stage. In the pre-production stage, it involves background research and creating the concept. In the production stage, it involves building intimacy with the subjects to gain trust for them. Finally in the post-production stage, it mingles with the visual and digital effects. The heterosexuals continue to have negative attitude towards LGBT because they view homosexuality a sin and immoral. The concept ?Sugakod ? was formulated because of the commonalities of the viewpoints of the third sex society as a whole. In Davao City, there are only few LGBTs who are willing to tell their tales because they are only members of the third sex society ? inferiority complex. In conclusion, the common standpoint of LGBTs are the struggle for equality, acceptance, and respect in the family, workplace and society. The eagerness to find a solution for a certain needs are more important than the aesthetic value of the film when communicating one's advocacy. ?Sugakod? was made to challenge the LGBT community to raise their marginalized voices and at the same time to challenge the heterosexuals to change their negative attitude towards LGBT.